Promosi Kesehatan Pre-Eklampsia pada Ibu Hamil di Desa Kenderan Kecamatan Tegalalang Kabupaten Gianyar - Putri, Samantha Lilian Tjipto; Sebastian, Putu Andrea Wisnu; Ghanaputri , Made Maharani Calistha; Yuliyatni, Putu Cintya Denny (Jurnal Pengabdian kepada Masyarakat Wahana Usada, 2024)
Background: Pre-eclampsia is multi-organ damage and occurs after the 20th week of pregnancy. The incidence of pre-eclampsia in Indonesia is very high compared to the global incidence, which is 10% in Indonesia compared to 2% globally. If not well managed, pre- eclampsia can lead to complications. Therefore, prevention is needed, which can be increased knowledge and early detection of pre-eclampsia. Purpose: To increase knowledge and understanding about preeclampsia in pregnant women. Method: The health promotion was conducted on 29 September 2023 by presentations using power point and interactive Q&A with the target all pregnant women in Kenderan village (40 people). Then, Blood pressure checks and prenatal exercises were conducted. Knowledge improvement was evaluated by comparing the pretest and posttest questionnaire responses. Results: Thirteen pregnant women (32.5%), attended this activity. The activity took place at the Kenderan village office (10.00-11.30 WITA). A comparison of pretest and posttest shows an average increase from 5.6 to 7.6 points. However, there are still correct answer that need improvement, specifically regarding the signs and symptoms of preeclampsia (76.9%) and pregnancy nutrition preeclampsia prevention (84.6%). Conclusion: The implementation of health promotion for preeclampsia among pregnant women has been successful. However, the number of participants who attended was lower than the target. Nonetheless, health promotion participants have shown an increase in their knowledge. The timing of the next activity should be better aligned with the availability of pregnant women's schedules. Additionally, the material should focus more on the signs, symptoms, and pregnancy nutrition related to prevention of preeclamsia.